2016
DOI: 10.1007/s00774-016-0749-8
|View full text |Cite
|
Sign up to set email alerts
|

Bone metabolism dysfunction mediated by the increase of proinflammatory cytokines in chronic HIV infection

Abstract: Despite the efficacy of antiretroviral therapy (ART) on the control of viral replication, the current challenge is to decrease the chronic inflammatory status and toxicity of the antiretroviral drugs that contribute to increase the risk of metabolic complications. To verify the influence of proinflammatory cytokines on bone metabolism mediated by chronic HIV infection, a cross-sectional study was conducted with 50 HIV-infected adult men treated or not treated with ART. Dual energy X-ray absorptiometry (DXA) wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 29 publications
0
17
0
1
Order By: Relevance
“…Meanwhile, IL-6 level in CD8 + T cells was obviously higher in the AS group than the other two control groups. Proinflammatory cytokine IL-6 is known to induce the activation of osteoclasts (35), which might closely relate to the bone metabolism associated with AS.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, IL-6 level in CD8 + T cells was obviously higher in the AS group than the other two control groups. Proinflammatory cytokine IL-6 is known to induce the activation of osteoclasts (35), which might closely relate to the bone metabolism associated with AS.…”
Section: Discussionmentioning
confidence: 99%
“…Several factors including sex, body mass index (BMI), vitamin D level, hormonal effects, smoking, alcohol drinking and HIV-related factors such as advanced HIV disease and low baseline CD4+ cell count may contribute to BMD loss among PLHIV [8][9][10][11][12]. Additionally, HIV-infection induced immune activation and chronic inflammation may alter bone formation activities by negatively affecting osteoclasts and osteoblasts functions [13][14][15][16]. Those activities can be measured by using bone resorption and bone formation markers such as c-telopeptide crosslink of type 1 collagen (CTX) and procollagen type 1 N-terminal propeptide (P1NP).…”
Section: Introductionmentioning
confidence: 99%
“…To explain the increase in osteolytic activity associated to HIV-1-induced bone loss, only a few mechanisms have been proposed: disruption of the immune system (6,18), increased production of proinflammatory cytokines (19), and direct infection of OC (20). Regarding the immune system, studies from the HIV-1-transgenic rat model revealed that bone damage results, in part, from an altered production of regulatory factors of osteoclastogenesis secreted by B cells (18).…”
mentioning
confidence: 99%